2006
DOI: 10.1016/j.jfoodeng.2005.06.065
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the fractionation of regular buttermilk and whey buttermilk by microfiltration

Abstract: The use of a ceramic microfiltration (MF) membrane for the fractionation of buttermilk and whey buttermilk obtained from pilot scale churning of cream and whey cream from industrial sources has been studied. Whey buttermilk contained comparable amounts of phospholipids compared to regular buttermilk but its protein content was lower due to the absence of caseins. However, it was found that lipid content of whey cream did vary significantly between lots resulting in important variations in the fat content of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
4
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 15 publications
5
66
4
9
Order By: Relevance
“…These fractions can be concentrated thanks to the development of micro and ultrafiltration technologies (Morin et al, 2006(Morin et al, , 2007a(Morin et al, , 2007bGassi et al, 2016). These compounds…”
Section: Mimicking Milk Fat Globule Coveragementioning
confidence: 99%
“…These fractions can be concentrated thanks to the development of micro and ultrafiltration technologies (Morin et al, 2006(Morin et al, , 2007a(Morin et al, , 2007bGassi et al, 2016). These compounds…”
Section: Mimicking Milk Fat Globule Coveragementioning
confidence: 99%
“…Sphingomyelin is primarily located in the outer membrane of the MFGM and is present in higher percentages in milk derived from cows fed with unsaturated fatty acids due to the presence of smaller globules and consequently more surface area (Lopez et al, 2008). Some studies indicate that starter cultures may contribute to the amount of PL, especially sphingomyelin, present in dairy products and by-products (Umemoto and Sato, 1973;Morin et al, 2006); however, another research group found similar sphingolipid concentrations in the raw material and the final fermented product, indicating that starter cultures do not contribute to SM in dairy foods (Ahn and Schroeder, 2002). In the contrary, they degrade some phospholipids, and thereby, explain the presence of phosphatidic acid in fermented foods.…”
Section: B) Sphingolipidsmentioning
confidence: 99%
“…Microfiltration features a pressure-driven membrane filtration, with pressure less than one bar and membrane pore size between 10 -1 -10 1 µm, which is commonly used for the removal of bacteria and separation of macro molecules (Corredig et al, 2003;Morin et al, 2006). In the dairy industry, this is employed to remove lipids from whey for production of whey protein concentrate (WPC).…”
Section: A) Microfiltrationmentioning
confidence: 99%
See 2 more Smart Citations